2014
DOI: 10.1177/0956797614534267
|View full text |Cite
|
Sign up to set email alerts
|

Are Orchids Left and Dandelions Right? Frontal Brain Activation Asymmetry and Its Sensitivity to Developmental Context

Abstract: To clarify long-standing conceptual and empirical inconsistencies in models describing the relation between frontal brain asymmetry and emotion, we tested a theory of biological sensitivity to context. We examined whether asymmetry of alpha activation in frontal brain regions, as measured by resting electroencephalography, is sensitive to early developmental contexts. Specifically, we investigated whether frontal asymmetry moderates the association between birth weight and adult outcomes. Adults with left fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
6
13
0
Order By: Relevance
“…In contrast, in the presence of positive environmental context, right frontal asymmetry was associated with more negativity; consistent with previous work in which right frontal asymmetry reliably characterizes negative affectivity (e.g. Schmidt, 1999; Fortier et al, in press). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, in the presence of positive environmental context, right frontal asymmetry was associated with more negativity; consistent with previous work in which right frontal asymmetry reliably characterizes negative affectivity (e.g. Schmidt, 1999; Fortier et al, in press). …”
Section: Discussionsupporting
confidence: 90%
“…An alternative explanation of our findings comes from emerging work (Fortier, Can Lieshout, Waxman, Boyle, Saigal, & Schmidt, in press) which suggests that resting frontal EEG asymmetry may be a biological factor indexing sensitivity to developmental context; essentially conceptualizing frontal asymmetry in terms of the differential susceptibility to environment theory (Belsky, Bakermans-Kranenburg, & Van IJzendoorn, 2007; Belsky & Pluess, 2009; Ellis et al, 2011). Fortier and colleagues found that adults who exhibited left frontal asymmetry and were born with extremely low birth weight (their measure of early developmental context) exhibited the highest levels of attention problems in adulthood, while adults with left frontal asymmetry who were born with a normal birth weight displayed the lowest levels of problem behaviors.…”
Section: Discussionmentioning
confidence: 92%
“…As can be observed from Figure , levels of shyness for relative left frontal asymmetry are relatively high across all participants, and control participants with relative left asymmetry have shyness levels comparable to maltreated participants. This finding is consistent with the notion that relative left frontal asymmetry supports both positive and negative emotional experiences (see Fortier et al., ), and it is possible that among control participants in our sample, left asymmetry is associated with negative emotionality. These results extend earlier work that has suggested that individual differences in resting frontal EEG asymmetry may serve as a differential susceptibility factor (Fortier et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the notion that relative left frontal asymmetry supports both positive and negative emotional experiences (see Fortier et al., ), and it is possible that among control participants in our sample, left asymmetry is associated with negative emotionality. These results extend earlier work that has suggested that individual differences in resting frontal EEG asymmetry may serve as a differential susceptibility factor (Fortier et al., ). Future research should examine the role of relative frontal asymmetry in the link between child maltreatment and additional social‐emotional outcomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation